The Effect of Wordwall Innovation Media on Descriptive Text Learning Outcomes of Class VII - Muhamad Topan Slamet Nurdin; Dida Firmansyah; Ika Mustika (JLER (Journal of Language Education Research), 2026)
Abstract This study employs a quasi-experimental design approach to identify characteristics. By using pre- and post-tests on the structure and linguistic components of descriptive texts written by seventh-grade students at SMP Taruna Bakti Bandung, this research aims to determine the impact of Wordwall learning media on learning outcomes. The research sample consisted of 27 students from Class VII E, while the research population included all seventh-grade students across nine classes. Class VII Bilingual 2, consisting of 24 students, was used as the control group. The data analysis process begins with assumption testing, requiring homogeneity and normality tests. Once the data were proven homogeneous and normal, hypothesis testing (t-test) was conducted. The study results showed that the experimental class achieved an average score of 84.15 in the t-test, while the control class, which did not receive treatment, scored an average of 72.42, indicating a considerable difference. A significant difference was found between the studied variables (2-tailed) 0.000 < 0.5. Therefore, Wordwall learning media significantly impacts students' learning outcomes in recognizing the characteristics, composition, and linguistic components of descriptive texts for seventh-grade students at SMP Taruna Bakti Bandung.